Histórias orais de docentes surdos acerca da apropriação da linguagem e as contribuições da língua de sinais - Filietaz, Marta Rejane Proença (2016)
This research aims to analyze the oral stories of deaf teachers in relation to the process of appropriation of the language and the contributions of Pounds for Constitution of your personal, professional and social development. The methodology chosen for the accomplishment of this study sought the theoretical assumptions based on research with qualitative approach. In this sense, if guided by a praxis with contributions on social-historical approach of dialectical nature, considering the historical and cultural trajectory of deaf teachers. Semi-structured interviews were made, passed through a process of translation from Portuguese pounds for the written, with six deaf teachers responsible for discipline in two federal institutions of higher education, being these the Federal Technological University of Paraná (UTFPR) and the Federal University of Paraná (UFPR). In the process of organizing the material for analysis were listed two major thematic units: the first Portuguese language's relations were discussed in writing mode, the Pounds and the other languages in the contexts of interaction of deaf guys, these being the family, school and social groups. The second thematic unit inserts reflections on the contributions of sign language for the deaf teacher development. By analyzing the aspects related to the processes of appropriation of language, from the memories of the participants of this study, it was possible to understand how sign language contributes to the personal, professional and social development, enabling deaf accessibility to goods and services produced in the different spheres of society, with an emphasis on studies in the field of education. The recognition of sign language as the language of the deaf community, brazilian means an ideological change with respect to the deaf that are recognized as different and belonging to a linguistic minority community, and not just a methodological change in the teaching and learning of a language. According to the participants of this study, the mobilization of deaf movements in the fight for recognition of their rights contributed heavily to new referrals, including the preparation and execution of public policies geared to the needs of these subjects. In view of the importance of the subject, it is suggested to conduct more studies in different institutions of higher education, both public and private, so how much more discussion can be extended from the knowledge of teaching deaf.